New Soliton Applications in Earth's Magnetotail Plasma at Critical Densities - Abdelwahed, Hesham G.; Abdelrahman, Mahmoud A. E.; İnç, Mustafa; Sabry, Refaat R. (Frontiers Media Sa, 2020)
New plasma wave solutions of the modified Kadomtsev Petviashvili (MKP) equation are presented. These solutions are written in terms of some elementary functions, including trigonometric, rational, hyperbolic, periodic, and explosive functions. The computational results indicate that these solutions are consistent with the MKP equation, and the numerical solutions indicate that new periodic, shock, and explosive forms may be applicable in layers of the Earth's magnetotail plasma. The method employed in this paper is influential and robust for application to plasma fluids. In order to depict the propagating soliton profiles in a plasma medium, the MKP equation must be solved at critical densities. In order to achieve this, the Riccati-Bernoulli sub-ODE technique has been utilized in solutions. The research findings indicate that a number of MKP solutions may be applicable to electron acoustics appearing in the magnetotail. AMS subject classifications:35A20, 35A99, 35C07, 35Q51, 65Z05
Keywords: MKP equation; explosive solutions; Riccati-Bernoulli sub-ODE method; plasma applications; magnetotail